The Eating At Treatment (Eat) Questionnaire: A Tool To Assess Habits Related To Patients Eating At Dialysis - Mary Burgess; Maria Stasios; Marcia Davis; Deborah Benner (The Korean Society of Nephrology, 2012)
Within the US, the policies at dialysis facilities differ as to whether patients (pts) are permitted to eat or not while being treated. The Eating At Treatment (EAT) pilot program was designed to determine whether educating pts and allowing them to eat on dialysis would reduce the number of missed meals on dialysis days and potentially improve nutritional status. The EAT questionnaire was developed as a tool to assess eating habits of pts on days they received dialysis treatment vs non-treatment days. Seven Registered Dietitians (RDs) administered the EAT questionnaire to 61 pts. Patients reported eating a different number of meals/day (2.32 vs 2.69) and snacks/day (1.09 vs 1.36) on treatment vs non-treatment days, respectively. Of the pts who ate at the dialysis facility, 86% reported that they ate during treatment as opposed to before or after treatment. Of the pts who did not eat at the dialysis facility, the most common reported reasons were that they were not hungry (63%) or reported an adverse event (eg., stomach pain, risk of diarrhea, hypotension) (20%). Reported dietary intake from 37 pts who ate during dialysis was scored by RDs for protein and kcal content. Adequate intake was set at > 200 kcal for calorie intake and > 10 g of protein for protein intake. Nineteen (51%) pts reported adequate kcal intake, while only 12 (32%) pts reported adequate protein intake. Based on results obtained from this small pilot questionnaire, pts reported eating less on treatment days vs non-treatment days. In addition, pts reported that their intake at treatment was low in protein. This questionnaire has proven to be an effective tool that is easy to administer and score (total time ∼12 min/pt) for providing insight into the eating habits of pts receiving dialysis treatment. An opportunity exists for educating pts through nutritional counseling about increasing their protein and kcal intake on treatment days. Distribution of this questionnaire to a large number of dialysis pts may prove useful for reevaluating policies regarding eating at dialysis centers.